ADSL technology in delivering broadband services: Telekom Malaysia's perspective / Shahida Shaharuddin - Shaharuddin, Shahida (2006)
The accelerated growth of content and multimedia-based applications that require high bandwidth has changed the nature of information network. High-speed communication is no longer perceived as a 'luxurious' item, in fact it becomes a 'necessity' these days. People crave for higher speed, fast downloading and bigger bandwidth in their daily undertakings; either for business purposes or pleasure. This new change of demand is a challenge to Telekom Malaysia (TM) in fulfilling customers' requirement and meeting their expectations. This project report will cover on TM's current practice in delivering broadband services to the mass public and on top of that, this project also will study the nature of ADSL performance as ADSL is known as a distance-sensitive technology.